Organocatalytic enantioselective desymmetrisation. (27th June 2016) - Borissov, A.; Davies, T. Q.; Ellis, S. R.; Fleming, T. A.; Richardson, M. S. W.; Dixon, D. J.
Abstract : Organocatalytic enantioselective desymmetrisation reactions efficiently create complex, enantioenriched frameworks from simple, inexpensive achiral or meso compounds. Abstract : Organocatalytic enantioselective desymmetrisation of achiral or meso compounds is a powerful strategy for the construction of enantiomerically enriched complex molecules, often with multiple stereocentres and in high selectivities. Recent years have seen increasing use of organocatalysts in desymmetrisation methodology, in contrast to traditional metal- or enzyme-catalysed reactions, with many impressive advances made in the current decade. This review will provide an overview of the field since 2010, with the aim of highlighting both the practical applications and elegance of enantioselective desymmetrisation to the wider synthetic community.